Research on Modeling and Suppression of the Tooth Profile Envelope Error of Non-circular Gear Hobbing - Han Jiang; Li Dazhu; Tian Xiaoqing; Xia Lian (Jixie chuandong)
The tooth profiles at different positions of the non-circular gear pitch curve have the characteristics of equal modulus but unequal curvature radius and polar diameter. The distribution characteristics of the envelope curve of each tooth profile formed during the hobbing process are different, which lead to the unequal envelope error of the tooth profile at different positions. Taking the basic linkage model of hobbing as the motion constraint, the geometric simulation scheme of the tooth profile generated by the intermittent cutting of the hob is constructed, and the correlation characteristics between the envelope distribution and the curvature radius of the pitch curve and the polar diameter are analyzed. The concept of equivalent hobs is introduced, the relationship model between envelope error and equivalent gear tooth number and equivalent hob groove number is built, and the calculation and position distribution of the maximum envelope error of different tooth profiles are analyzed. A hobbing model to improve the envelope error is proposed. The model can realize the change of the equivalent hob groove number at different positions of the non-circular curve through the hob shifting method, thereby the maximum value and uneven distribution of the envelope error are improved. This study provides theoretical support for the analysis of the tooth profile envelope error of the non-circular gear hobbing, which can predict the envelope error and guide the formulation of a reasonable machining plan.